De pennas vacillantes em mãos infantis à produção do jornal O Bem-ti-vi: culturas do escrito e crianças de elites em Caetité, BA (1899-1914) - Giane Araújo Pimentel Carneiro (2021)
This research aimed to analyze a children's newspaper – O Bem-ti-vi – in order to understand the relationship between the elite children and the cultures of the writing, between 1899 and 1914, in the city of Caetité-BA. We have analyzed how the newspaper's production took place, investigating, as Darnton (1990) proposed, the printed material circuit produced from the author to its (probable) reader. Knowing what were the existing written materials, what readings were carried out by the writers and collaborators, what place the writing occupied in the lives of these elite children, what the newspaper materiality informs about their production, mainly, about which were the probable targeted readers and empirical readers, are some issues that prompted us to carry out this study. For this purpose, we have used the collection of this newspaper that circulated fortnightly, for approximately two years in the city of Caetité. Family letters, news from newspapers, memorialist works, were used as complementary sources. Much of this documentation is available at the Municipal Public Archive of Caetité. The newspaper had as “head writers” the children Mario Teixeira Rodrigues Lima and Anísio Spínola Teixeira, who were born in elite traditional families, which held economic, social and cultural capital. The proposal to study the intertwining of the history of written culture with the history of children in the first decades of the 20th century is justified by the singularity of the place occupied by children in this historical period and by the low visibility of the theme in Research. We can affirm that reading and writing practices were very present among children, especially in the elite families. The typographical aspects showed a newspaper with a good impression, praised for its “good finish”. This undertaking was part of an actions set to “follow the progress”, because in Caetité it was not enough for the elites to be and appear distinct, an effort was made so that the city itself would be recognized for the distinction in all its aspects. The installation of two schools in Caetité – Escola Americana and Colégio São Luiz – in 1912, the republication of the newspaper A Penna in late 1911 and the support of families raised the boys' motivation, in addition to providing conditions to produce the newspaper itself. The newspaper O Bem-ti-vi addressed the Caetitéense society and the region, with the explicit aim of contributing to children education and with the intention that each one of them would become a “good republican citizen”, for Bahia “recovery” and the Sertão progress.